Efficacy of topical acne agents in the treatment of Acne Vulgaris: Insights from a meta-analysis - Adeola Tawakalitu Kola-Mustapha (Pensoft Publishers, 2023)
Topical therapies are essential for controlling Acne Vulgaris because they have specific therapeutic effects on the skin. Through a meta-analysis, this study seeks to determine the effectiveness of topical acne treatments in the management of Acne Vulgaris. Data extraction and systematic study of literatures were both included in the methodology utilized for this meta-analysis. Controlled clinical trials and randomized controlled trials comparing topical acne treatments with placebos were included as inclusion criteria. The search strategy used techniques for assessing the quality of results, additional sources, and electronic databases. The pooled effect sizes and publication bias were computed using a random effects model. The results were presented as effect estimates, confidence ranges, and significance levels. The RR estimate for the common effect model is 5.1986, and the 95% confidence interval is [3.8070; 7.0990]. According to this, persons who receive topical acne treatments have a 5.1986 times higher chance of getting a good result than those who receive a placebo. Overall, there isn't much proof of publication bias in the meta-analysis of topical pharmaceutical therapies for Acne Vulgaris, according to the findings of the linear regression test of funnel plot asymmetry. These results provide useful insights into the use of topical treatments for Acne Vulgaris and highlight the targeted mechanism of action, rigorous clinical study designs, consideration of heterogeneity, and statistical significance of the topical acne agents.